Religious Practices among Muhammadiyah Citizens during the Covid-19 Pandemic - Rahmat Efendi; Nihayati Nihayati (Cakrawala: Jurnal Studi Islam, 2021)
The purpose of this study is to describe how committed and loyal Muhammadiyah members are at the branch level to the PP Muhammadiyah's official statement about religious practices during the COVID-19 pandemic. Data was collected through observation, interviews, and documentation in this descriptive qualitative study. The findings of this study show that residents follow PP Muhammadiyah's edict not to practice religious agenda and to "close" mosques. Second, following the transition period, residents have returned to the mosque to worship as they did prior to the pandemic (without using health protocols). Third, large-scale agenda (such as tabligh akbar) have not yet been conducted, but small-scale agenda have been conducted face-to-face, rather than virtually.